تقييم المناعة الأمية لدجاج اللحم ضدَّ مرض فقر الدّم المعدي - فاضل, محمد; العابد, صبا (Latakia University Journal -Biological Sciences Series, 2015)
تُقيم هذه الدّراسة المناعة الأمية لمرض فقر الدّم المعدي عند صيصان دجاج اللحم . فقد تمّ تربية مجموعتين من صيصان دجاج اللحم بعمر يوم واحد ،أُخذت المجموعة الأولى من قطيع أمات محصن ضدَّ مرض فقر الدّم المعدي ، والمجموعة الثانية من أمات غير محصنة ضدَّ المرض . وتمَّ إجراء اختبار المقايسة المناعية المرتبط بالأنزيم (الاليزا) لقياس معيار الأضداد المناعية لمرض فقر الدّم المعدي لدى هذه الصيصان . جُمعت عينات الدّم من الصيصان كل خمسة أيام، بدءاً من اليوم الأول من العمر. وأظهرت نتائج الدراسة أن متوسط معيار الأضداد لصيصان المجموعة الأولى كان (3344)، في حين كان متوسط معيار الأضداد لصيصان المجموعة الثانية ( 4144) في اليوم الأول من العمر، وقد أظهرت النتائج أيضاً انخفاضاً في مستوى الأضداد خلال 15 يوماً، وقد أثبتت هذه الدراسة انتشار المرض في القطعان غير المحصنة. This study evaluates the maternal immunity to chicken anemia virus in broiler chicks. Two groups, of only one day old chicks, have been breeding . The first group was obtained from a vaccinated breeder flock against chicken anemia virus .The second one was obtained from unvaccinated breeder flock against the same disease. Blood samples were collected from the chicks every five days starting from the first day of their birth. The test was performed enzyme –linked immunoassay (ELISA) to measure antibody titer for chicken anemia virus in these birds. The research results have shown that the average antibody levels for the first group was (3344) for the one day old chicks while (4144) for the second group. The results have also shown that there was a decrease in the average antibody levels during 15 days. This research has proved prevalence of disease in unvaccinated flock